engaruh Massa Pati Terhadap Tensil Strength, Elongasi dan Daya Serap Terhadap Air pada Pembuatan Bioplastik dari Pati Sagu dan Gliserol - Rozzana Rozzana; Nurhaliza Nurhaliza; Saifullah Ramli; Syahiddin Syahiddin; Abrar Muslim (Universitas Syiah Kuala, 2022)
Bioplastics are a type of plastic made from renewable biomass sources. The purpose this research is to make bioplastics that function as shopping bags, where the procedure making bioplastics uses solution casting method by using starch weight variation 6; 8 and 10 grams and glycerol ratio variation is 1.5; 2 and 2.5 grams as plasticizers. Bioplastics with the best tensile strength test are combined with pectin solution where pectin mass variation is 0.25; 0.5; 0.75; 1; 1.5 and 2 gram obtained tensile strength values respectively, 0.48 kgf / mm2; 0.95 kgf / mm2; 1.37 kgf / mm2; 3.84 kgf / mm2; 3.36 kgf / mm2 and 3.44 kgf / mm2 while the percent elongation value is 4.34%; 6%; 5.7%; 40.85; 14.35% and 6.85%. The lowest water resistance value is found in bioplastics with the addition of 6 grams of starch and glycerol 2.5 grams while the highest value of water resistance is obtained from bioplastics with the addition of 10 grams of starch and 2.5 grams of glycerol. Bioplastic characterization was performed using the Fourier Transform Infra-Red (FTIR) test. This research provides information about the characterization of sago and glycerol-based bioplastic functional groups marked with C-O, C-H, C = O and O-H groups in each FTIR spectrum region